2019
DOI: 10.1080/24740527.2019.1678113
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the effectiveness of an acceptance and commitment therapy–based bibliotherapy intervention among adults living with chronic pain

Abstract: Background: Chronic pain has a significant impact on the physical and psychological functioning of those living with this condition. It is now recognized that acceptance and commitment therapy (ACT) is an effective intervention in managing chronic pain; however, several barriers limit its accessibility. Aims: The current study aimed to evaluate the effectiveness of an 8-week bibliotherapy-type self-administered psychological intervention with minimal therapeutic contact, based on ACT, in the management of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Specifically, all but one of the studies demonstrated random sequence generation [48]. On allocation concealment, one study was assessed as "high risk of bias" [55], eight studies were assessed as "unclear risk of bias" [42,43,45,46,48,50,53,54]. For performance bias, all studies were considered "low risk of bias."…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, all but one of the studies demonstrated random sequence generation [48]. On allocation concealment, one study was assessed as "high risk of bias" [55], eight studies were assessed as "unclear risk of bias" [42,43,45,46,48,50,53,54]. For performance bias, all studies were considered "low risk of bias."…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Moreover, no evidence of serious bias was found. For detection bias, six studies did not explicitly indicate whether they blinded the interviewers and were therefore assessed as "some concerns" [47,54,56,57,59,60]. In terms of attrition bias, twenty studies were rated as "low risk of bias" [28, 29, 46, 47, 49-51, 53, 55-57, 60].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A recent review recommended the use of ACT self-help as an intervention, especially when combined with clinician guidance (French et al, 2017). ACT bibliotherapy has shown promise in a case-series evaluation of those with MS (Harrison et al, 2017) and a robust trial in chronic pain (Veillette et al, 2019). A review examining the efficacy of psychotherapy delivered over the telephone in MS showed moderate benefits in physical and mental health domains, with the authors recommending further studies of better quality (Proctor, Moghaddam, Vogt, et al, 2018).…”
Section: Acceptance Based Telephone Support Around the Time Of Transi...mentioning
confidence: 99%
“…One such intervention type is bibliotherapy, or the therapeutic use of books and other reading materials ( Bilich et al, 2008 ; Howie, 1988 ) which can be used to address psychological and physical health concerns ( Hedman et al, 2016 ). Among them, bibliotherapy has been used to provide support for internalizing type problems, such as depression and anxiety ( Lorenzo-Luaces et al, 2023 ), and managing a number of long-term conditions including: chronic pain ( Thorsell et al, 2011 ; Veillette et al, 2019 ), appearance related concern ( Muftin and Thompson, 2013 ; Powell et al, 2023 ), distress associated with multiple sclerosis ( Proctor et al, 2018 ) and in post-stroke management ( Gladwyn-Khan and Morris, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…ACT’s efficacy in cancer has been reported in face-to-face therapy studies ( Arch and Mitchell, 2016 ; Brown et al, 2020 ; Gentili et al, 2019 ; Gonzalez-Fernandez et al, 2018 ; Li et al, 2021a , 2021b ; Low et al, 2016 ). Further ACT bibliotherapy’s potential is seen in other conditions, including irritable bowel syndrome (IBS) ( Gillanders et al, 2017 ), skin and appearance-related conditions ( Powell et al, 2023 ), multiple sclerosis ( Proctor et al, 2018 ) and chronic pain ( Veillette et al, 2019 ) with similar effects observed in non-clinical populations, too ( Jeffcoat and Hayes, 2012 ; Ritzert et al, 2016 ). However, to our knowledge there is no existing research that has examined the acceptability of ACT for individuals with cancer delivered in the form of bibliotherapy.…”
Section: Introductionmentioning
confidence: 99%